The Shikhara - Temples of India Project Team (Jio Institute, 2024)
The shikhara (superstructure) stands as a fusion of architectural elements, where a towering vertical spire intertwines with the half spires and the miniature spires. The central offset is embellished with the surasenaka (pediment made of chaitya dormer), crowned by a kirtimukha (face of glory) at its zenith.